Atypical Breast Proliferative Lesions and Benign Breast Disease (Springer International Publishing, 2018)
The days of surgical excision for any atypical lesion have been replaced by more nuanced decision making and individualized patient management. Current management of many of these lesions continues to be controversial in regard to observation with close surveillance versus the need for surgical excision of these lesions based on future risk or whether these lesions are precursor lesion. The goal of this book is to provide a concise but comprehensive review of atypical breast proliferative lesions and their management complexities. New data about breast cancer, risk factors for breast cancer, pathological features unique to each entity, the characteristic findings on imaging, risk stratification for genetic testing, as well as the current evidence-based management of each of these breast lesions are discussed in full detail. Assessment tools for risk prediction of breast cancer are also highlighted as chapters run the gamut of current imaging modalities, as well as advanced screening options available for diagnosis and following these patients. Atypical Breast Proliferative Lesions and Benign Breast Disease will undoubtedly become a valuable resource for nurse practitioners, physician assistants, breast and surgical oncology fellows, genetic counselors, geneticists, as well as other clinicians and surgeons who are referred and manage these complex breast patients. All chapters in this text are written by experts in the field who have research and clinical interest in each of these disease entities, and include the most up-to-date research and clinical information to enhance our understanding and treatment of patients.